1994
DOI: 10.1016/s0923-2494(94)80181-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of autoimmunity and AIDS: prospects for therapeutic intervention

Abstract: The network theory of autoimmunity is presented with recent experimental data relevant to the understanding of the pathogenesis of AIDS. Schematically, effector T cells specific for self-antigens exist normally, but their activity is modulated and prevented by networks of regulatory T cells. As a result of mimicry between molecular components of microorganisms and self-antigens, autoimmune disease can be triggered by specific foreign pathogens which alter the state of activity of the network from suppression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 103 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…In fact the concept of alloimmunization for HIV indication has been promoted by many research groups for more than a decade but it has never received due consideration [39][40][41][42][43]. It is hoped that the new experimental evidence that became available recently will change this situation.…”
Section: Monkey Wrench: Alloimmunization As a Strategy For Aids Prevementioning
confidence: 99%
See 1 more Smart Citation
“…In fact the concept of alloimmunization for HIV indication has been promoted by many research groups for more than a decade but it has never received due consideration [39][40][41][42][43]. It is hoped that the new experimental evidence that became available recently will change this situation.…”
Section: Monkey Wrench: Alloimmunization As a Strategy For Aids Prevementioning
confidence: 99%
“…Indeed, the vaccination with alloantigens as the immune basis for preventive vaccination has been advocated by many reputable immunologists [36][37][38][39][40][41][42][43]. The positive data from Abalaka's experiments and placebo-controlled trial results with V-1 Immunitor suggest that allovaccination has good chances of success and needs to be investigated further [49,50,61].…”
Section: New Embodiment For Rsa Immunotherapy: Therapeutic Aids Vaccinementioning
confidence: 99%
“…The opinion that AIDS is an autoimmune disease and alloimmunization is perhaps the answer to the problem has been expressed by many researchers over the last two decades [150][151][152][153][154][155][156][157][158][159]. If it is correct, then the prevailing AIDS vaccine strategy, which is directed away from the alloimmunization concept, may be flawed.…”
Section: Autoimmune and Alloimmune Aspects Of Hiv Diseasementioning
confidence: 99%
“…T-cell vaccination has been studied in experimental animals (Ben-Nun et al, 1981;Cohen, 2000;Lider et al, 1988), and lately has been used clinically to induce the downregulation of human autoimmune diseases such as multiple sclerosis (Zhang et al, 1993;Cohen, 2002;Zhang et al, 1995Zhang et al, , 2000. Atlan and colleagues have previously suggested that autologous anti-CD4 T-cells might be used as vaccines to down-regulate anti-CD4 autoimmunity in HIVinfected patients (Atlan et al, 1993(Atlan et al, , 1994Atlan and Cohen, 1996).…”
Section: Introductionmentioning
confidence: 99%